CEO confidence and stock returns. Issue 1 (April 2016) - Bharati, Rakesh; Doellman, Thomas; Fu, Xudong
Abstract: Consistent with the theoretical predictions of Goel and Thakor (2008), we find that overconfident CEOs create significant value for the firm through superior stock return performance and take more risk, compared to their non-overconfident counterparts. We also differentiate between innovative and non-innovative industries and find for each subsample that overconfident CEOs create firm value. We find these results even when we control for founder CEOs as they add value and make similar corporate policy decisions as overconfident CEOs. Finally, consistent with the predictions of Goel and Thakor (2008), we find that overconfident CEOs are hired less frequently, take less risk, and add less value after the enactment of the Sarbanes–Oxley Act in 2002, which put in place strict penalties for poor quality information disclosures by corporations. This finding has significant implications for empirical study as this paper provides evidence of the important impact the Sarbanes–Oxley Act has on the relation between CEO overconfidence and firm policies.